2017
DOI: 10.1111/scs.12467
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender, working field and psychosocial factors on the vulnerability for burnout in mental hospital staff: results of an Austrian cross‐sectional study

Abstract: Gender had a differential effect on perceived occupational stress indicating a need for gender-tailored preventive strategies. Age, working field, education, voluntarily occupational training during holidays and length of stay on job affect vulnerability for burnout in mental hospital staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
(65 reference statements)
2
17
2
Order By: Relevance
“…Female nurses experienced more Cy than male nurses; nurses who worked <40 hr per week reported less Cy; and psychological demand was positively associated with Cy. In contrary to us, Schadenhofer et al () reported higher Cy among men. They explained the reason for their finding that female nurses often establish a deeper relationship with patients and have lower levels of Cy (Schadenhofer et al, ).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Female nurses experienced more Cy than male nurses; nurses who worked <40 hr per week reported less Cy; and psychological demand was positively associated with Cy. In contrary to us, Schadenhofer et al () reported higher Cy among men. They explained the reason for their finding that female nurses often establish a deeper relationship with patients and have lower levels of Cy (Schadenhofer et al, ).…”
Section: Discussioncontrasting
confidence: 84%
“…In contrary to us, Schadenhofer et al () reported higher Cy among men. They explained the reason for their finding that female nurses often establish a deeper relationship with patients and have lower levels of Cy (Schadenhofer et al, ). But, Li et al () did a study among 1,559 nurses in five hospitals of Shenyang, China, and found that female nurses reported more than 2 times cynicism compared to males (Li et al, ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…As there is evidence for gender differences in coping with stress, it was assumed that perception of job‐related meaningfulness differs between female and male nurses (e.g., enhanced empathic capabilities in women – Tomova, von Dawans, Heinrichs, Silani, & Lamm, ). There is some evidence that nurses’ resources to prevent occupational stress are affected by age (Cheng, Chen, Chen, Burr, & Hasselhorn, ), length of stay on job (Kudo et al., ; Schadenhofer, Kundi, Abrahamian, Stummer, & Kautzky‐Willer, ), and their education (Brunetto et al., ; Norlund et al., ).
Hypothesis 2: Perception of job‐related meaningfulness is influenced by socio‐demographic attributes such as gender, age, length of stay on job, and education.
…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the isolated analysis of the dimensions, and low personal fulfillment (PF) between 18.8% and 93.7% (14) . (15)(16) . In fact, the care process peculiar aspects contribute to the feminization of some occupations and professions, as observed in the health sector (15) .…”
Section: Methodsmentioning
confidence: 99%